PENGARUH METODE PEMBELAJARAN SCRAMBLE TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA MATA PELAJARAN IPS KELAS III SDN 88 SINGKAWANG - Pitri Handayani; Nindy Citroresmi Prihatiningtyas; Andika Kusuma Wijaya; Fajar Wulandari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims: 1) To determine the differences in cognitive learning outcomes between students in the experimental class using the scramble method and students in the control class using the conventional method in third grade at SDN 88 Singkawang; 2) To determine the extent of the influence of the scramble learning method on the cognitive learning outcomes of third-grade students at SDN 88 Singkawang. The research design used was post-test only. The population consisted of all third-grade students at SDN 88 Singkawang, totaling 48 students. The research instruments included a post-test on cognitive learning outcomes in Social Studies and a Lesson Plan. The prerequisite tests applied normality and homogeneity tests with a significance level of 5% (0.05), and hypothesis testing was conducted using a two-sample t-test and effect size analysis. The results showed that the t-test obtained t-count = 4.059 and t-table = 2.012, where t-count > t-table (4.059 > 2.012), indicating that Ha was accepted. This shows that there is a difference in the cognitive learning outcomes in Social Studies between the experimental and control classes. The effect size test result was 1.68, indicating that the scramble learning method had a high category influence on the cognitive learning outcomes of students.